Desinfestação, estabelecimento e calogênese in vitro de Paubrasilia echinata Lam E. Gagnon, H. C. Lima & G. P. Lewis - Mariano, Gustavo Fernandes (2024)
The species Paubrasilia echinata, known worldwide as pau-brasil and considered the national tree of Brazil, is a tree species belonging to the Fabaceae family and native to the Atlantic Forest. P. echinata is endangered due to intense exploitation, driven by the high demand for its wood during the colonial period in Brazil, making it necessary to develop strategies for its conservation, propagation, and reforestation, especially considering its representative role in the Atlantic Forest biome. In this context, in vitro propagation or micropropagation emerges as an excellent alternative for the species' preservation. However, native species face challenges in establishing in vitro due to the difficulty of disinfecting biological material (explants) to eliminate microorganisms originating from the field. These microorganisms, usually bacterial or fungal in nature, can proliferate excessively in the in vitro environment and lead to the death of the explant. Tests with different explants, different exposure times, and different concentrations of conventional disinfecting agents (alcohol and sodium hypochlorite), as well as new methodologies such as the use of silver nanoparticles (AgNPs), have been developed to improve the disinfection technique of explants and favor the in vitro establishment of tree species like pau-brasil. Therefore, the present study aimed to test the disinfecting agents sodium hypochlorite (NaClO) from the Qboa® brand, silver nanoparticles (AgNPs), and their combination, at different exposure times (5- 30 min) and concentrations (60 and 100%) using fruits, seeds, and axillary buds as explants for the disinfection and callogenesis induction stages with P. echinata from leaflets of in vitro plants and zygotic embryos with different growth regulators (2,4-D, Dicamba, and Picloram). The results showed that the disinfection of P. echinata fruits treated in a solution containing only NaClO and Manzate® fungicide had contamination rates below 25%, with the lowest percentage of contamination. For in vitro germination percentage, the values reached 75% compared to the other explants and treatments containing NaClO and AgNPs, offering more effective disinfection and a more suitable in vitro establishment of the species, providing in vitro biological material for various uses and purposes in in vitro propagation. For callogenesis induction, the formation of non-embryogenic calli was observed in all treatments